ASSESSING THE IMPACT OF FLIPPED CLASSROOM ON MATH COMPREHENSION IN PRIMARY SCHOOL STUDENTS - Nala Khilmi; Siswanto Siswanto; Purwanto Purwanto (Universitas Majalengka, 2024)
This study aims to evaluate the effectiveness of the Flipped Classroom learning model in improving the understanding of mathematical concepts in elementary school students. Using a quasi-experimental design with a pre-test and post-test nonequivalent control group design, data were collected from 50 sixth graders of an elementary school. The Flipped Classroom model is compared to conventional teaching methods, with students' understanding of mathematical concepts as dependent variables. Results showed significant improvements in both groups, signaling the positive impact of both teaching methods on student understanding. However, no significant differences were observed between the two methods. The study emphasizes the importance of considering a variety of factors, including technology skills, parental support, and cultural context, in choosing the right teaching method. While the Flipped Classroom offers an innovative approach, conventional methods remain relevant in specific contexts. Recommendations for future research include the use of larger samples and considering additional factors that affect learning outcomes. Overall, the research contributes to an understanding of effective teaching practices in basic mathematics education, providing valuable insights for educators and policymakers.